Molecular epidemiology and decreased susceptibility to disinfectants in carbapenem-resistant Acinetobacter baumannii isolated from intensive care unit patients in central China - Jing Guo; Congrong Li (Elsevier, 2019)
Background: Infection with carbapenem-resistant Acinetobacter baumannii (CRAB) is an increasing problem for critically ill patients. The srains are frequently resistant to all antibiotics and disinfectants are often used to block the spread of these bacteria, playing an important role in infection control. Objectives: The aim of this study was to investigate the antibiotic susceptibility, the clonal relationship, disinfectant resistance gene, β-lactamase genes and the disinfectant sensitivity of 82 A. baumannii isolates collected at a large hospital in Wuhan, China. Design: A retrospective basic study. Methods: Here we investigated 82 A. baumannii isolates from intensive care unit patients in a major teaching hospital in China for the distribution of resistance-associated genes and susceptibility to chlorine disinfectant (CLR), benzalkonium bromide (BB) and Chlorhexidine gluconate(CHG). Multi-locus sequence typing (MLST) was applied to explore their genetic evolution relationships. Results: qacE (30.48%, 25/82) and qac△E1 (76.82%, 63/82) genes were detected in our study, while none were positive for qacA/B, qacC/D or qacG. The MIC values of CLR were 250 mg/L; The MIC values ranged from 32 to 128 μg/mL for BB; The MIC values ranged from 0.0019% to 0.0078% for CHG. The presence or absence of qacE gene has a significant impact(p ＜ 0.05) on MICs of BB or CHG. All isolates harboured blaOXA-51/23 genes, and 98.78% of isolates contained the ISaba1 insertion sequence. All isolates were classified into 8 sequence types(STs) within clonal complex 92(CC92). Conclusions: The predominant CRAB strains in our intensive care unit are blaOXA-23-containing A. baumannii of CC92. The high prevalence of qac genes and reduced susceptibility to disinfectants confirm the need for continued vigilance against nosocomial infections. Keywords: Carbapenem-resistant Acinetobacter baumannii, OXA β-lactamases, Disinfectants, Multi-locus sequence type